Digitalization in Business: Examining the Antecedents of Repurchase Intention Using Traveloka Application - Rosdiana Sijabat (Jurnal Manajemen Indonesia, 2020)
In the current technological development, internet and smartphone users in conducting transactions online continue to experience growth. This development is mainly in the entertainment and leisure industry to provide opportunities for businesses to create an application in the field of online travel, one of which is Traveloka. This study aims to analyze the impact of information quality, application design, and satisfaction on repurchase intention with social media engagement as a mediating variable. Data were collected deploying the non-probability sampling method through online questionnaires, 400 responses were received and 392 included for data analysis. Research participants were the general public who had used the Traveloka application previously. Structural equation modelling (SEM) has been used to examine the association of the constructs, including information quality, application design, satisfaction, social media engagement and repurchase intention. The results indicate that the quality of information, application design, payment methods, and security and privacy had a positive and significant effect on customer satisfaction. Social media engagement does not statistically significant mediates the impact of information quality and application design on repurchase intention in the Traveloka application. Keywords— Information quality; mobile application; intention to repurchase; application design; social media engagement.